8. The Total of Leukocytes Mice (Mus musculus) Exposed To Secondhand Smoke Extract And Given Watermelon (Citrullus vulgaris) - Dewi Mauliza; Rusli Rusli; Roslizawaty Roslizawaty; Rosmaidar Rosmaidar; Rinidar Rinidar; Dian Masyitha (Jurnal Medika Veterinaria, 2018)
This study aimed to determine the effect of the red watermelon extract can affect the number of leukocytes in mice exposed to cigarette smoke. This study was designed with a completely randomized design using a unidirectional pattern 20 male mice (Mus muscullus) were divided into 4 groups. K1 negative controls were given 0.5 ml of distilled water, K2 positive control by exposure to cigarette smoke and 0.5 ml of distilled water, K3 by exposure to cigarette smoke and red watermelon extract were given a dose of 22 mg / mouse and K4 by exposure to cigarette smoke and were given extracts of red watermelon a dose of 44 mg / mouse. Exposure to cigarette smoke and red watermelon extract conducted for 30 days, making blood on day 31. Blood sampling performed at Plexus Retroorbitalis. Furthermore, counting the number of leukocytes. Data were analyzed using ANOVA completely randomized design with SPSS for Windows 16.0. The results of this study showed that the extract of watermelon for 30 days showed their real influence (P 0.05) to the number of leukocytes in mice. It is concluded that free radicals contained in cigarette can cause a leukocytosis, an inflammatory, oxidative stress and red watermelon extract can minimize cell damage.